(untitled) (Medical Forum Monthly, 2024)
Objective: To observe and compare placental histology for hypoxic changes in diet plus exercise alone versus diet plus exercise and insulin treatment in patients with Gestational Diabetes Mellitus (GDM). Study Design: Comparative / analytic study. Place and Duration of Study: The study was conducted in Lyari General Hospital and Mamji Hospital after approval from the Institutional Review Board (IRB) and Ethical Committee of Dow University of Health Sciences from Jan 2010- Jan 2011. Materials and Methods: After written informed consent, 30 patients were diagnosed to have GDM with RBS between 126-129mg/dl were given diet control plus exercise therapy (Group A). 39 GDM patients with RBS greater than 130 mg/dl were kept on diet plus exercise and insulin (Group B). After delivery placentae were collected from 25 patients in each group. Histological slides of placentae were prepared and parameters of hypoxia such as villous immaturity, villous fibrinoid necrosis, syncytial knots, chorangiosis, calcification etc. were observed and compared between the two groups using light microscope. Results were evaluated by SPSS 16 using student t- test and chi square test. Results: Statistically non-significant results were obtained for the hypoxic parameters. However numerically more calcification was found in Group A while villous immaturity, villous fibrinoid necrosis and syncytial knots were present more in Group B. Conclusion: Histological examination of placentae showed presence of hypoxic features in both Group A and Group B patients with more propensities in diet plus exercise and insulin treated GDM group.